Traumatic orbital fractures and various approaches to their treatment - R. . Ronchevich; Z. . Savkovich; R. T. Nigmatullin (Российский офтальмологический журнал)
Traumatic fractures of the orbit are fairly frequent injuries both in wartime and in peacetime. The purpose of the paper is to present the modern view of orbital lesions and their consequences, based on literary data and the authors’ personal experience. Surgical treatment consisting in the reconstruction of the original orbital shape and volume and in repositioning of orbital contents to their previous location is the only correct method of treating these injuries, which has to be resorted to as soon as possible. In cases of neglected fractures of orbital walls and edges, we need to refracture the bone, reposition and fix the broken orbital fragments, and then, concomitantly, reconstruct the orbital shape and volume as well as reposition the orbital contents in their original location. In patients with neglected orbital fractures, the results of surgical treatment (correction of eye position, enophthalmos, and double vision) are considerably poorer than those achieved after surgical treatment of fresh injuries. In reconstructing the orbital wall, autologous transplants are used (the cranial bone, the ilium, the bone of the front wall of the maxillary sinus, constal cartilage) as well as a variety of alloplastic materials // Russian Ophthalmological Journal, 2016; 3: 101-9. doi: 10.21516/2072-0076-2016-9-3-101-109.